Genome-wide screens implicate loss of Cullin ring ligase 3 in persistent proliferation and genome instability in TP53-deficient cells - Drainas, Alexandros Panagiotis; Lambuta, Ruxandra A.; Ivanova, Irina; Serçin, Özdemirhan; Sarropoulos, Ioannis; Smith, Mike L.; Efthymiopoulos, Theocharis; Raeder, Benjamin; Stütz, Adrian M.; Waszak, Sebastian Martin; Mardin, Balca; Korbel, Jan Oliver (Cell reports, 2020)
TP53 deficiency is the most common alteration in cancer; however, this alone is typically insufficient to drive tumorigenesis. To identify genes promoting tumorigenesis in combination with TP53 deficiency, we perform genome-wide CRISPR-Cas9 knockout screens coupled with proliferation and transformation assays in isogenic cell lines. Loss of several known tumor suppressors enhances cellular proliferation and transformation. Loss of neddylation pathway genes promotes uncontrolled proliferation exclusively in TP53-deficient cells. Combined loss of CUL3 and TP53 activates an oncogenic transcriptional program governed by the nuclear factor κB (NF-κB), AP-1, and transforming growth factor β (TGF-β) pathways. This program maintains persistent cellular proliferation, induces partial epithelial to mesenchymal transition, and increases DNA damage, genomic instability, and chromosomal rearrangements. Our findings reveal CUL3 loss as a key event stimulating persistent proliferation in TP53-deficient cells. These findings may be clinically relevant, since TP53-CUL3-deficient cells are highly sensitive to ataxia telangiectasia mutated (ATM) inhibition, exposing a vulnerability that could be exploited for cancer treatment.